Molecular mechanisms of ARMC5 mutations in adrenal pathophysiology - Stratakis, Constantine A. (Curr Opin Endocr Metab Res, 2019)
Since the initial discovery of mutations in the Armadillo-containing repeat protein 5 gene (ARMC5) in primary bilateral macronodular adrenocortical hyperplasia (PBMAH), efforts have been made to better understand the molecular mechanisms involving ARMC5 in the development of this rare form of Cushing syndrome. It has now been established that germline ARMC5-inactivating mutations, mostly frameshift and nonsense ones, are responsible for roughly 40% of PBMAH cases. ARMC5 is a tumor suppressor gene responsible for a familial form of PBMAH. Furthermore, the presence of inactivating ARMC5 mutations is associated with a more severe CS and hypertension as well as an overall increase in adrenal mass. However, ARMC5 inactivation decreases cortisol secretion both in vitro and in vivo (in mice) suggesting that the way that ARMC5 deficiency leads to Cushing syndrome is complicated and maybe not a direct effect of the ARMC5’s loss, requiring additional molecular events to take place. Moreover, in silico predicted damaging ARMC5 variants have been identified in patients of African American descent with primary aldosteronism suggesting a potential role of ARMC5 in predisposing to low renin hypertension. Beyond its role in adrenocortical cells, ARMC5 defects has recently been associated with meningioma and T-cell immune response defects in humans and mice, respectively. Herein, we review recent discoveries in ARMC5’s role in adrenal pathophysiology and beyond; clearly, we are only at the beginning of understanding the function of this gene with functions in the adrenal gland, the immune system, and elsewhere.